Glycosylation-on-a-Chip: A Flow-Based Microfluidic System for Cell-Free Glycoprotein Biosynthesis - Aquino, Alicia K.; Manzer, Zachary A.; Daniel, Susan; DeLisa, Matthew P. (Frontiers in Molecular Biosciences, 2021)
In recent years, cell-free synthetic glycobiology technologies have emerged that enable production and remodeling of glycoproteins outside the confines of the cell. However, many of these systems combine multiple synthesis steps into one pot where there can be competing reactions and side products that ultimately lead to low yield of the desired product. In this work, we describe a microfluidic platform that integrates cell-free protein synthesis, glycosylation, and purification of a model glycoprotein in separate compartments where each step can be individually optimized. Microfluidics offer advantages such as reaction compartmentalization, tunable residence time, the ability to tether enzymes for reuse, and the potential for continuous manufacturing. Moreover, it affords an opportunity for spatiotemporal control of glycosylation reactions that is difficult to achieve with existing cell-based and cell-free glycosylation systems. In this work, we demonstrate a flow-based glycoprotein synthesis system that promotes enhanced cell-free protein synthesis, efficient protein glycosylation with an immobilized oligosaccharyltransferase, and enrichment of the protein product from cell-free lysate. Overall, this work represents a first-in-kind glycosylation-on-a-chip prototype that could find use as a laboratory tool for mechanistic dissection of the protein glycosylation process as well as a biomanufacturing platform for small batch, decentralized glycoprotein production.